2019
DOI: 10.1111/aphw.12169
|View full text |Cite
|
Sign up to set email alerts
|

Best Practice Guidelines and Essential Methodological Steps to Conduct Rigorous and Systematic Meta‐Reviews

Abstract: Background: A growing body of primary study and systematic review literature evaluates interventions and phenomena in applied and health psychology. Reviews of reviews (i.e., meta-reviews) systematically synthesise and utilise this vast and often overwhelming literature; yet, currently there are few practical guidelines for meta-review authors to follow. Objective: The aim of this article is to provide an overview of the best practice guidelines for all research synthesis and to detail additional specific cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 61 publications
0
66
0
Order By: Relevance
“…As primary research as well as systematic reviews and meta‐analyses grow exponentially each year, the need to systematically synthesize the evidence‐base by conducting a meta‐review has grown as well (also known as an overview or review of reviews ; as argued elsewhere, the term “meta‐review” has the advantage of being relatively precise as the term literally means “review of reviews”; in contrast, “overview” could refer to a large number of possibilities) . Meta‐reviews can serve several purposes, including to compare and contrast the findings from systematic reviews and to provide a summary of the evidence and the quality of the evidence across these reviews . Along with the rapid growth of meta‐reviews, there are numerous methodological tools and considerations, many of which are still in the early phases of development or for which there are no established guidelines .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As primary research as well as systematic reviews and meta‐analyses grow exponentially each year, the need to systematically synthesize the evidence‐base by conducting a meta‐review has grown as well (also known as an overview or review of reviews ; as argued elsewhere, the term “meta‐review” has the advantage of being relatively precise as the term literally means “review of reviews”; in contrast, “overview” could refer to a large number of possibilities) . Meta‐reviews can serve several purposes, including to compare and contrast the findings from systematic reviews and to provide a summary of the evidence and the quality of the evidence across these reviews . Along with the rapid growth of meta‐reviews, there are numerous methodological tools and considerations, many of which are still in the early phases of development or for which there are no established guidelines .…”
Section: Introductionmentioning
confidence: 99%
“…Overlap of the primary‐level studies in meta‐reviews is one such area for consideration and an important one for evidence synthesis methodologists because it concerns the potential for non‐independence in the primary studies across similar reviews. The extent to which systematic reviews in a particular domain include the same studies varies widely, depending on many factors . On the one hand, if reviews address similar questions with similar methods and integrate largely the same primary‐level studies' results, then their review conclusions should not differ.…”
Section: Introductionmentioning
confidence: 99%
“…As an emerging tool, meta-review can be an important method to summarize a broad and heterogeneous literature [9]. As some researchers have argued, "meta-reviews, which pull together existing synthesis literature, can have tremendous influence on research, practice, and policy; indeed, if conducted appropriately, synthesis literature is considered the strongest level of evidence, with meta-reviews atop the evidence pyramid" [10].…”
Section: Introductionmentioning
confidence: 99%
“…2). After deduplication 198 remained, and after screening abstracts and full text, seven were included [16][17][18][19][28][29][30]. One additional conference citation was found through expert knowledge on the topic [31], and one paper recently published was included after completion of the rst draft [32].…”
Section: Screening Resultsmentioning
confidence: 99%
“…The authors found that when overviews contain overlapping primary studies, selecting a Cochrane systematic review, as opposed to the most recent or highest quality non-Cochrane review, maximized the amount of outcome data included in the overview [18]. Pollock [19,30] Murphy [23] Patnode [33] Select one (or more) reviews using prespeci ed eligibility criteria Ballard [28]; Hennessy [16,29]; Pollock [17];…”
Section: Characteristics Of Methods Studiesmentioning
confidence: 99%